Developing bullying prevention guidelines for nurse interns' and its effects on their assertiveness - Lobna S. Abou El yazied; Rabab M. Hassan; Fawzia M. Badran (BMC, 2024)
Abstract Background Bullying is a serious problem that has short and long term negative consequences for nurse interns. Bullying prevention guidelines have a great impact on reducing the incidence of bullying among nurse interns. Aim The present study aimed to evaluate the effect of developing bullying prevention guidelines on nurse interns' assertiveness levels. Methods A methodological study design was used to conduct the study at Ain Shams University Hospitals in Cairo Governorate, Egypt. The study subjects consisted of all nurse interns enrolled in the 2022-2023 internship year and their number 121 nurse interns. The data were collected using four tools: the Bullying Knowledge Questionnaire, the Negative Act Questionnaire Revised (NAQ-R), the Individual Bullying Behaviors in Clinical Practice Survey, and the Assertiveness Inventory. Results The scores for total bullying knowledge and assertiveness after the implementation of the prevention guidelines were significantly increased (91.4% and 86.3%, respectively) among those who were exposed to bullying than among those with pretest scores of (34.7% and 11.8% respectively) (P < 0.001). Conclusion Bullying prevention guidelines significantly reduced nurse interns bullying and improved their assertiveness. The study recommended the dissemination and generalization of the developed bullying prevention guidelines in different training settings.